G52(P) Very early onset inflammatory bowel disease – a single centre experience. (27th April 2016) - Hambleton, LK; Kirkham, S; Shah, N; Kammermeier, J; Devadason, D
Abstract : Introduction: There is evidence to suggest that Very Early Onset Inflammatory Bowel Disease (VEOIBD) runs a more aggressive course when compared to older children with inflammatory bowel disease and may not respond to conventional therapy. Aim: To study outcomes and disease course in children with VEOIBD (6 years and under at the time of diagnosis) in the era of established biological therapy. Method: A retrospective descriptive analysis was performed on patients with VEOIBD at the Queen's Medical Centre, Nottingham. These children were identified using the database and corroborated by clinician recall and histopathology records. We then analysed the medical notes, documenting diagnosis, histology findings, growth parameters, immune work-up, clinical course and management. Results: We identified 12 patients with VEOIBD diagnosed between March 2011 and December 2014. 7 were male (58%). The median age at diagnosis was 3 years 6 months. Of our cohort: 5 had indeterminate colitis, 4 had a phenotype of Crohn's disease and 3 had a phenotype of ulcerative colitis. The median duration of follow up is 15.5 months (4 mo - 56 mo). Of particular interest 75% of this cohort were born to non-British born parents, possibly indicating that the aetiology of VEOIBD may be related to a rapidly changing microbiome interacting with the innate and adaptive immune system. 3 of the 12 patients were considered to have severe disease (all males), with one of these cases having proceeded to bone marrow transplant and two further cases currently being considered for bone marrow transplant. 9 children received methylprednisolone at diagnosis to induce remission often followed by weaning of oral steroids. 9 children received Azathioprine. 4 received infliximab, 1 of whom progressed onto Adalimumab and Sirolimus in combination. At latest follow-up 9 out of the 12 children were considered to be in remission. Conclusion: We describe the clinical course of children with VEOIBD. Histopathological diagnosis into Crohn's disease and UC is more difficult in this group and early work up for monogenic disease is recommended for planning individualised treatment. VEOIBD is a distinct and heterogeneous category of bowel inflammation, the incidence of which is rising and more likely to affect children born to recent immigrant families.